Efektivitas Standar Operasional Prosedur Laboratorium dalam Pembiasaan Perilaku Positif Siswa Sekolah Dasar - Hanif Anwar; Junaidin (Mataram University, 2026)
Character building from an early age represents a pivotal focus within primary education curricula. This study examines the efficacy of implementing school laboratory Standard Operating Procedures (SOPs) as a structural stimulus to condition positive student behaviors, including discipline, accountability, hygiene, and integrity. Utilizing a qualitative approach with a descriptive case study design, this paper analyzes the transition of written SOP regulations into automated habits (habituation). This analysis is framed through the integration of Thomas Lickona’s character development framework and B.F. Skinner’s operant conditioning theory. The field results demonstrate that the consistent enforcement of laboratory regulations significantly reduces the frequency of student indiscipline. The primary determinants of successful internalisation include the assertiveness of teacher enforcement, the availability of representative facilities, teacher modeling, and cohesive monitoring collaboration between schools and parents. This study recommends restructuring conventional SOP formats into child-friendly visual media and integrating a system of positive reinforcement to cultivate intrinsic compliance among elementary school students.